Cancel the Deal? An Experimental Study on the Exploitation of Irrational Consumers - Cappelen, Alexander W.; Meissner, Stefan; Tungodden, Bertil (Management Science, 2025)
Consumers can sometimes be exploited because they make mistakes in their valuation of products. We present the results from a large-scale experimental study that examines whether third-party spectators from the general population in the United States cancel a voluntary deal where a buyer has made a mistake in the valuation of a product and agreed to pay more for the product than the seller knows it is worth. We find that the majority of the spectators cancel such deals, even when the seller’s involvement is limited to accepting a proposal made by the buyer. A substantial share of these spectators is also willing to fine the seller. However, a large minority of the spectators are willing to uphold the deal even when the seller has proposed the deal and obfuscated the information provided to the buyer. Our results shed new light on when people view market transactions as acceptable and their attitudes to government regulation of businesses. This paper was accepted by Axel Ockenfels, behavioral economics and decision analysis. Funding: This project was financed with support from the Norges Forskningsråd [Centres of Excellence Scheme Centre for Experimental Research on Fairness, Inequality and Rationality Project 262675 Grants 236995, 250415, 262636, and 302145]. The project also received funding from the European Research Council [the European Union’s Horizon 2020 Research and Innovation Programme Grant 788433]. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2023.01050 .